Synergistic impacts of propargite exposure and deformed wing virus infection on the health of western honey bees - Lin, Chia-Yang; Lin, Yu-Chun; Lu, Yun-Heng; Chen, Shiang-Jiuun; Lin, Yu-Hsien; Tseng, Yao-Kuang; Lin, Yu-Tzu; Wu, Yueh-Lung; Huang, Rong-Nan (Ecotoxicology and environmental safety, 2025)
This study aimed to elucidate the possible synergistic effects of chemical pesticides and viral infections. Our experiments demonstrated that the Varroa mite-borne deformed wing virus (DWV) by itself had a minimal impact on bees. Conversely, when bees were simultaneously treated with acaricides, their mortality rate increased. The administration of DWV alone boosted the expression of immune response genes, whereas acaricide alone did not significantly affect the expression of detoxification genes. However, simultaneous treatment of DWV and acaricide increased both the immune response and detoxification gene expression, thereby indicating enhanced bee resistance. These findings indicate a synergistic association between viral infection and bee sensitivity to acaricides, possibly as a result of physiological or immune system impairment. Our results also indicated that adenosine supplementation enhances the resilience of bees to environmental challenges, further supporting the energy requirement hypothesis. [Display omitted] •Combined biological and non-biological stressors increased bee mortality.•Stressors significantly raised carbohydrate levels in bee hemolymph.•Energy supplementation boosted bee resilience to environmental stressors.